Comparison of three different adhesive joints using static and dynamic impact tests : Development of a new drop weight impact test rig incorporating a modified Arcan fixture. (April 2022) - Maurel-Pantel, A.; Voisin, M.; Mazerolle, F.; Lebon, F.
Abstract: The paper proposes to compare static and dynamic properties of three structural adhesives selected for the integration of optical space systems. These comparisons are based on an original methodology using static test and drop weight impact test to determine the best shock-strength candidate. In a first section, the design of the drop weight impact rig integrating a modified Arcan fixture is described. Then validity of the impact test rig is discussed on a simplified case thanks to an analytical model of "soft impact" available in literature. In a second section, static tests results are presented and the adhesive's critical stresses are identified with a point stress criterion. Finally, impact tests results are used to discuss the dynamic tensile and shear behaviour of each adhesive with different stress concentrations. Static critical stresses and impact strengths of the adhesives are reported. In conclusion a strategy of adhesive choice is discussed.